The challenges of financing small and medium scale enterprises (SMEs). A case of the Trust Bank Limited. - Opoku, Diana (2014)
A thesis submitted to the School of Business, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Business Administration.